Circadian rhythm disruption-mediated downregulation of Bmal1 exacerbates DSS-induced colitis by impairing intestinal barrier - Zhang, Zhongchao; Li, Wanneng; Han, Xu; Tian, Dean; Yan, Wei; Liu, Mei; Cao, Li (Frontiers in Immunology, 2024)
Background: Circadian rhythm disruption (CRD) is thought to increase the risk of inflammatory bowel disease. The deletion of Bmal1, a core transcription factor, leads to a complete loss of the circadian rhythm and exacerbates the severity of dextran sodium sulfate (DSS)-induced colitis in mice. However, the underlying mechanisms by which CRD and Bmal1 mediate IBD are still unclear.We used a CRD mouse model, a mouse colitis model, and an in vitro model of colonic epithelial cell monolayers. We also knocked down and overexpressed Bmal1 in Caco-2 cells by transfecting lentivirus in vitro. The collected colon tissue and treated cells were assessed and analyzed using immunohistochemistry, immunofluorescence staining, quantitative reverse transcription-polymerase chain reaction, western blotting, flow cytometry, transmission electron microscopy, and terminal deoxynucleotidyl transferase-mediated dUTP nick-end labelling staining Results: We found that CRD mice with downregulated Bmal1 expression were more sensitive to DSS-induced colitis and had more severely impaired intestinal barrier function than wild-type mice.Bmal1-/-mice exhibited more severe colitis, accompanied by decreased tight junction protein levels and increased apoptosis of intestinal epithelial cells compared with wild-type mice, which were alleviated by using the autophagy agonist rapamycin. Bmal1 overexpression attenuated Lipopolysaccharide-induced apoptosis of intestinal epithelial cells and impaired intestinal epithelial cells barrier function in vitro, while inhibition of autophagy reversed this protective effect.This study suggests that CRD leads to the downregulation of Bmal1 expression in the colon, which may exacerbate DSS-induced colitis in mice, and that Bmal1 may serve as a novel target for treating inflammatory bowel disease.